Influence of metal surface structure on the anisotropic XPS - Changshi, Liu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The intensive distribution of photoelectrons as a function of X-ray beam with variable angle of incidence was investigated. Diffraction caused by the structure of surface was observed in the following metal samples: Al with face-centered cube, Ta and W with body-centered cubes. No effect was observed in Fe and Cu samples. The effect is closely related to the anode high voltages and X-ray energy. There was a range of threshold values in which the surface structure effects could be defined in experimental high voltages of anode. The possible mechanism of this effect was discussed.
Optica Applicata, Vol. 35, 2005, nr 2, s. 409-413
Keywords: optyka; high voltage of anode; structure of surface; X-ray photoelectron spectroscopy (XPS)